Promise me [large type] - Evans, Richard Paul (Thorndike Press large print core, 2010)
Beth Cardall's life was falling apart: her six-year-old daughter, Charlotte, was suffering from an unidentifiable illness; her marriage transformed from a seemingly happy and loving relationship to one full of betrayal and pain; her job was increasingly at risk; and she had lost her ability to trust, to hope, or to believe in herself. Then, on Christmas day, Beth encountered Matthew.